Perancangan Ulang Tata Letak IKM Tahu Sehat Sari untuk Mengurangi Jarak Material Handling - Fadilah, Andara; Hikam , Azka; Muhtar , Dini; Anom , Mauli; Rifai, Achmad Pratama (Fakultas Teknik Universitas Tulang Bawang, 2025)
Small and Medium Enterprises (SMEs) typically operate within limited or small spaces, with production activities that are sometimes mismatched with their available conditions. This includes the Tahu Sehat Sari SME case, where the existing product layout results in significant material handling movement, leading to high operational costs. This research designs a facility layout tailored to the SME’s needs. The layout is developed considering various constraints such as cost, available area, and other resources. The goal of this design is to create a new production layout for Tahu Sehat Sari SME, accommodate its relatively high daily production capacity, to minimize operational costs, reduce material handling distances, and increase productivity. Based on the initial layout of the SME, proposed layouts using methods such as Modified Spanning Tree (MST) and Simulated Annealing (SA) are compared. From the layout designs using single-row Simulated Annealing, double-row Simulated Annealing, and Modified Spanning Tree, the total material handling distances calculated are 8,590, 1,950, and 1,695, respectively, with the total material handling distances in the current layout 2,600 m. The most suitable layout design is determined based on the minimization of total travel distance, directly correlating to the optimization of material handling and the elimination of waste. Keywords: Double Row, Layout Planning, Modified Spanning Tree, SimulatedAnnealing, Single Row